Geological characteristics of deep coal rock and main geological factors controlling coalbed methane enrichment: a case study of the M area in the eastern Ordos Basin - Xiaojiao GUO; Lei WANG; Xianzhou YAO; Xu LI; Linke ZHANG; Xiaoshuang WANG (Shiyou shiyan dizhi)
The 8# thick coal seam is widely distributed with high organic matter thermal maturity at the top of the Upper Carboniferous Benxi Formation in the M area of the Ordos Basin. However, the coal seams in this area are characterized by large burial depth, rapid lateral changes, strong heterogeneity, and unclear basic geological features and enrichment patterns of deep coalbed methane (CBM). The criteria for selecting favorable targets are yet to be established. These severely restrict the efficient exploration of deep CBM. To promote increased reserves and efficient production of deep CBM, and to further develop the enrichment theory of deep CBM in the eastern Ordos Basin, a comprehensive study was conducted based on core observations, experimental tests, scanning electron microscopy, well logging data from 76 wells in the study area, and 3D seismic data. The geological characteristics of deep coal seams and the main controlling factors of CBM enrichment were investigated, preliminary clarifying the exploration potential of this area. The results indicate that: The 8# coal seam at the top of the Upper Carboni-ferous Benxi Formation in the M area of the Ordos Basin is mainly composed of coking coal and lean coal, which are medium to high-ranked coals. The thickness of bright coal and semi-bright coal ranges from 2 to 6 m. Organic components are mainly vitrinite, accounting for 79.8%. Industrial components exhibit medium to high levels of volatile matter and ash, abundant fixed carbon, and low moisture content. The coal rock reservoir has well-developed pores and fractures, primarily composed of micropores and macropores. Gas content ranges between 16-25 m3/t. The enrichment of deep CBM in the eastern margin of the Ordos Basin is mainly controlled by coal reservoir and structural factors. Favorable exploration areas for deep CBM include regions with coal seams thicker than 6 m, areas with developed fractures far from fault zones (fault displacement less than 5 m), and microstructure high points. Based on these criteria, a favorable exploration area of 207 km2 for the 8# coal seam was identified, with 97 km2 classified as Type Ⅰ and 110 km2 as Type Ⅱ.